2017
DOI: 10.5897/ajb2016.15820
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and optimization of lipase activity produced by Pseudomonas monteilli 2403-KY120354 isolated from ground beef

Abstract: A total of 56 Gram negative bacterial isolates were recovered from twenty ground beef samples and were screened for their potentiality to produce lipase. Forty four bacterial isolates were recorded as positive producers for lipase on tween as carbon source in solid medium. Also, the highly producer isolates were screened for lipase activity in submerged culture using olive oil as carbon and the most active isolate was 2043 which gave an activity of 20.0 ± 0.29 U/ml. The bacterial isolate 2403 was identified ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Furthermore, the presence of these metallic ions that are naturally found in meat, may enhance the activity of certain lipases [41]. Importantly, nitrite-free sausages had the highest pH among analysed batches that is closest to the optimum activity of many microbial lipases (pH from 6 to 9) [42,43].…”
Section: Chemical Analysesmentioning
confidence: 99%
“…Furthermore, the presence of these metallic ions that are naturally found in meat, may enhance the activity of certain lipases [41]. Importantly, nitrite-free sausages had the highest pH among analysed batches that is closest to the optimum activity of many microbial lipases (pH from 6 to 9) [42,43].…”
Section: Chemical Analysesmentioning
confidence: 99%
“…The result obtained from the effect of temperature on activity and stability indicated the optimum temperature of LipAMS8 was like that of soluble enzyme which shows highest activity at lower temperature and diminishes as the temperature increases as it evident in other cold-active Pseudomonas lipase (Salwoom et al, 2019). Various research conducted reported the optimum temperature of Pseudomonas lipase within the range of (30 0 C-45 0 C) (Abdel-Hamied et al, 2017). LipAMS8 CatIBs half-life in this current study revealed its high stability to withstand long duration of incubation up to 10 hours with significant residual activity up to 50%.…”
Section: Effect Of Temperature On Activity and Stability Of Lipams8 C...mentioning
confidence: 50%
“…As shown in Table 2, the highest production of lipase (225 U/ml) was recorded for strain 3 after 24 h; thus, it was selected for further study. In a parallel study by Rasmey et al (2017), it was reported that the highest lipase activity (20.0 ± 0.29 U/mL) was recorded for Pseudomonas monteilii using olive oil as the substrate in the medium. Similarly, the highest lipase activity (2.33 ± 0.12 U) was indicated by Staphylococcus sp.…”
Section: Resultsmentioning
confidence: 97%
“…Lo Giudice et al (2006) studied the effectiveness of different isolated bacteria for their lipolytic activity on Tween and tributyrin by hydrolytic plate assay, and they reported that among the strains tested for lipid hydrolysis, only 7 isolates were unable to utilize the media, while the remaining hydrolyzed at least one substrate, and the diameters of the halos were generally 9–29 mm using Tween. In a parallel study, Rasmey et al (2017) reported that among the 56 tested isolates, only 24 isolates were recorded as lipase producers with lipolytic zone diameters of 18–32 mm.…”
Section: Resultsmentioning
confidence: 99%